Magnetization of active inclusion bodies: comparison with centrifugation in repetitive biotransformations - Koszagova, Romana; Krajcovic, Tomas; Palencarova-Talafova, Klaudia; Patoprsty, Vladimir; Vikartovska, Alica; Pospiskova, Kristyna; Safarik, Ivo; Nahalka, Jozef (Microbial cell factories, 2018)
BACKGROUND: Physiological aggregation of a recombinant enzyme into enzymatically active inclusion bodies could be an excellent strategy to obtain immobilized enzymes for industrial biotransformation processes. However, it is not convenient to recycle "gelatinous masses" of protein inclusion bodies from one reaction cycle to another, as high centrifugation forces are needed in large volumes. The magnetization of inclusion bodies is a smart solution for large-scale applications, enabling an easier separation process using a magnetic field. RESULTS: Magnetically modified inclusion bodies of UDP-glucose pyrophosphorylase were recycled 50 times, in comparison, inclusion bodies of the same enzyme were inactivated during ten reaction cycles if they were recycled by centrifugation. Inclusion bodies of sialic acid aldolase also showed good performance and operational stability after the magnetization procedure. CONCLUSIONS: It is demonstrated here that inclusion bodies can be easily magnetically modified by magnetic iron oxide particles prepared by microwave-assisted synthesis from ferrous sulphate. The magnetic particles stabilize the repetitive use of the inclusion bodies .
Keywords: Active inclusion bodies; Sialic acid aldolase; biotransformace; Biotransformation; Centrifugation; Magnetic modification; UDP–glucose pyrophosphorylase; centrifugace; Recycling in biotransformations; buněčná inkluze; Inclusion Bodies